Respostas

2013-12-13T11:25:20-02:00
log 8 na base 2 + log 25 na bse 5 + log 49 na base 7 + log 1 na base 7

1°)
log 8 na base 2 = x  --> 2 elevado x = 8 --> 2 elevado x = 2 elevado 3 , x=3
2°)
log 25 na bse 5 = a  --> 5 elevado a = 25 --> 5 elevado a = 5 elevado 2 , a=2
3°)log 49 na base 7
=b --> 7 elevado b = 49 --> 7 elevado b = 7 elevado 2, b=2
4° log 1 na base 7
=c --> 7 elevado c = 1 --> 7 elevado c = 7 elevado 0 , c=0

assim :

log 8 na base 2 + log 25 na bse 5 + log 49 na base 7 + log 1 na base 7 = 3+2+2+0=7



1 1 1
muito obrigada pela ajuda valeu ..